The Contribution of Limb Muscle Explosive Power To Soccer Heading Skills At The Andeskal Club Of Bengkulu City - Dwingki Marta Putra; Deffri Anggara (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the contribution of leg muscle explosive power to heading skills at the Andeskal Club in Bengkulu City. This type of research is correlational research. The research sample is 30 people. The instrument used in this study was a test of explosive power on heading ability. Based on the results of the above study, there is a contribution of leg muscle explosive power to heading skills at the Andeskal Club of Bengkulu City, that leg muscle explosive power to heading skills at the Andeskal Club of Bengkulu City is 42.25%, which means that leg muscle explosive power contributes to heading skills in soccer game.